STRATEGIES AND CHALLENGES OF WOMEN’S PARTICIPATION IN INCREASING POLITICAL REPRESENTATION IN 2024 (A Study of the Gerindra Party in Bandung City) - Bayu Septiansyah; Toto Kushartono; Lukman Munawar Fauzi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Women’s political participation constitutes a fundamental indicator of inclusive and gender-equitable democracy. Although Law Number 7 of 2017 on General Elections mandates that political parties allocate at least 30% of legislative candidacies to women, local political dynamics continue to reveal a persistent gap between descriptive and substantive representation. This study examines the strategies and challenges of the Gerindra Party in Bandung City in enhancing women’s political representation in the 2024 Election. This research employs a qualitative descriptive-analytical approach, drawing on in-depth interviews, observation, and document analysis. The analytical framework integrates Hanna Pitkin’s theory of political representation and Anne Phillips’ concept of the politics of presence. The findings demonstrate a substantial increase in women’s descriptive representation within the Gerindra faction of the Bandung City Council, rising from 12.5% (2019–2024) to 42.9% (2024–2029). Despite this quantitative progress, substantive representation remains constrained by structural and cultural barriers, including entrenched patriarchal norms, unequal access to political resources, and limited leadership development opportunities. The study concludes that numerical gains in representation must be accompanied by institutionalized empowerment mechanisms to ensure meaningful political influence. Transforming the politics of presence into the politics of influence requires sustained party reform, systematic cadre development, and the cultivation of a gender-inclusive political culture.